The Symbolic Meaning of the Nuei Rasan Tradition among the Kaur Community in Bengkulu Province - Fadel Ilham Susanto; Hertika Sari; Rossi Delta Fitranah (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Marriage in traditional societies is not merely a biological bond and formal legal contract, but a life cycle rich in socio-cultural values and ancestral traditions. This study aims to deeply examine the Nuei Rasan tradition, which lives and is preserved within the Padang Guci community in Selika Village, Kaur Regency, Bengkulu Province. The focus of the study is directed at four main aspects: the procession of execution, functions and purposes, educational values (local wisdom), and religious values contained within it. This research utilizes a qualitative descriptive approach with an ethnographic method. Data were gathered through observation techniques, in-depth interviews with customary leaders and tradition practitioners, and text documentation. The results indicate that the Nuei Rasan tradition is a form of matchmaking deliberation involving customary mediators as well as specific instruments such as down payments and palai money, which distinguishes it from the customs of other tribes. Customary equipment such as tongking, betel leaf, lime, areca nut, and lemang are not merely visual complements, but symbols of honor, sincerity, etiquette, and customary legality. Socially, this tradition constructs values of politeness and social order for the younger generation. Theologically, this tradition manifests gratitude to Allah SWT and strengthens harmonious community friendship bonds.